René Gerónimo Favaloro (1923–2000): A Man Who Struggled with Matters of the Heart. Issue 1 (January 2018) - Rubenstein, Robyn; Cowan, Scott W.; Yeo, Charles J.; Entwistle, John W.
René Gerónimo Favaloro prided himself on being a "simple country doctor." Born in La Plata, Argentina, Dr. Favaloro had an interest in Argentina's sociopolitical and healthcare systems beginning at a young age. He began his medical education at La Universidad Nacional de La Plata, graduating in 1949 with plans to continue his medical education in the field of surgery; however, in 1950, Dr. Favaloro temporarily resigned from his position as a surgeon to work as a country doctor in a small province of La Pampa, Argentina. It was during this time that Dr. Favaloro became acutely aware of the overwhelmingly poor state of the healthcare system in Argentina. In 1962, Dr. Favaloro redirected his focus back to his surgical interests and moved to the United States to work at the Cleveland Clinic, where he discovered the use of the saphenous vein graft for revascularization of the coronary arteries. Despite a productive medical career in the United States, Dr. Favaloro eventually brought his work back to Argentina, where his heart had always remained. Throughout the incredible milestones of his life, Dr. René Gerónimo Favaloro consistently remained a humble, gracious, and simple country doctor.